Model-based assessment of longitudinal dynamic performance and energy consumption of heavy haul train on long-steep downgrades - Shi, Jin; Ren, Shujing; Zhang, Mengran (Transport, 2019)
Longitudinal dynamics performance and energy consumption of heavy haul train should be considered in the design of heavy haul railway profile of long-steep downgrades. A quantitative analytical tool is developed to assess the longitudinal dynamic performance and energy consumption of heavy haul trains with large axle loads on grades with different longitudinal profiles, including a longitudinal dynamic model of the train and a method of calculating the energy consumption during the operation of heavy haul train. The model is then preliminarily validated by the data of coupler force collected in two comprehensive tests. Finally, the proposed analytical tool is used to assess the designed longitudinal track profile of a long-deep downgrade segment of the central south heavy haul railway of Shanxi (China).